2018
DOI: 10.1371/journal.pone.0193600
|View full text |Cite
|
Sign up to set email alerts
|

Use of the ureteral access sheath during ureteroscopy: A systematic review and meta-analysis

Abstract: The debate still rages on for the usefulness of ureteral access sheath (UAS). Therefore, a meta-analysis to discuss the effects of applying UAS during ureteroscopy was performed. The protocol for the review is available on PROSPERO (CRD42017052327). A literature search was conducted up to November, 2017 using the Web of science, PUBMED, EMBASE and Cochrane Library. The quality of articles was assessed by the Jadad scale and Newcastle Ottawa Scale (NOS). Egger’s test and the trim-and-fill method were used to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 29 publications
2
26
2
8
Order By: Relevance
“…A previous systemic review and meta-analysis by Huang et al showed no difference in SFR, operative time and intraoperative complications with the use of UAS although the post-operative complications were slightly higher with its use [28]. Our prospective data of consecutive patients with renal stones show similar results in both groups although with a slightly higher operative time in patients with UAS owing to higher stone size, multiplicity and the time taken to insert the sheath itself.…”
Section: Discussionsupporting
confidence: 70%
“…A previous systemic review and meta-analysis by Huang et al showed no difference in SFR, operative time and intraoperative complications with the use of UAS although the post-operative complications were slightly higher with its use [28]. Our prospective data of consecutive patients with renal stones show similar results in both groups although with a slightly higher operative time in patients with UAS owing to higher stone size, multiplicity and the time taken to insert the sheath itself.…”
Section: Discussionsupporting
confidence: 70%
“…[19] Despite being controversial and a lack of overwhelming support, UAS is widely used in RIRS. [20] The guidelines of the European Association of Urology have no clear recommendations for UAS usage, whereas the American Urological Association guidelines recommend the use of a UAS when performing RIRS for complex, high-volume renal stones. [21,22] The natural ureteral lumen is 9-F, narrower than any UAS on the market.…”
Section: Discussionmentioning
confidence: 99%
“… 52 In fact, a systematic review of ureteral access sheaths reports an association with increased risk of postoperative complications. 53 The concern for renal pelvic pressures stems from the notion that persistent pressures in excess of normal range may be attained during ureteroscopy and that this may increase the risk of postoperative infection. Although there are currently no systematic studies supporting these practices, we propose that it is good clinical practice to limit operative time and to endeavor to maintain low irrigation pressures as well as consistent decompression of the upper urinary tract.…”
Section: Preventionmentioning
confidence: 99%